Kov a coastal ecotourism center promoting a culture of stewardship in Barangay Pundaquit, Zambales - Teng, Grant Gregory T.; Varona, Maria Faith Y. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Kov is a coastal ecotourism development which aims to establish Barangay Pundaquit in San Antonio, Zambales, Philippines as a prime in-land cove and island exploration jump-off point while promoting stewardship and responsibility in the use and enjoyment of Pundaquit;s natural resources to the tourism sector and the local community of Pundaquit. The project aims to bridge the gaps between the local community, tourists, government, and the private sector by utilizing a holistic approach in addressing the needs of each stakeholder. Kov features spaces and facilities geared towards empowering the community into recognizing their goal in the care, ownership, and responsibility towards the natural and built environment of Barangay Pundaquit.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Ecotourism development -- Zambales -- Philippines; Ecotourism center